Estimate of cold plasma on antibiotic resistance and biofilm formation in Staphylococcus aureus isolated from clinical cases - Zainab Sabah Fahim; Majid Kadhim Aboud Al Shibly ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2025)
Background: Staphylococcus aureus is a commensal and opportunistic bacterium and the leading cause of human bacterial infections worldwide. S. aureus exhibits significant resistance to antibiotics, particularly methicillin-resistant Staphylococcus aureus (MRSA) strains. This resistance is a growing global concern, as S. aureus can rapidly adapt to various antibiotic treatments, making these bacteria difficult to treat. The ability to form biofilms enhances this resistance, allowing S. aureus to persist in infections and become resistant to antibiotics. Therefore, alternative treatment options to antibiotics are needed to control antibiotic resistance and biofilm formation, and cold plasma may be an alternative. Objective: This study aimed to evaluate the effect of cold plasma on S. aureus antibiotic resistance and its ability to form biofilms. Methodology: 100 clinical samples were collected, isolated, and identified. S. aureus isolates were exposed to cold plasma for different time periods (3, 6, and 9 minutes). Changes in susceptibility to several antibiotics were assessed using the disk diffusion method. A biofilm formation assay was also performed using crystal violet staining. Results: The results demonstrated the clear effectiveness of cold plasma against S. aureus antibiotic resistance and ability to form biofilms. The effectiveness of the tested antibiotics was increased, while the bacteria lost their ability to form biofilms by 100%. The results support the idea of ​​using cold plasma technology as an alternative to antibiotics to eliminate pathogenic and antibiotic-resistant bacteria, and thus treat some diseases associated with these bacteria. Conclusion: The results demonstrated the potential of using cold plasma technology as an alternative to antibiotics to treat diseases associated with S. aureus.